(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
With this work, we seek to put ourselves in dialog, in a writing that is guided by the circuit of affections (Safatle, 2016) and qualitative research in the affective dimension (Moriceau; Soparnot, 2019), with the book Dead Girls, by Argentine writer Selva Almada. Our proposal is to trigger notions of temporalities, bodies and affections, through authors who reflect on everyday life and ordinary events (Das, 2020; Lingis, 2018; Stewart, 2007), narratives (Jácome, 2020; Ricoeur, 1994) and the challenges of countering the romanticization of journalism (Carvalho, 2019). We bring into the discussion three researchers on gender violence: Caldeira (2017), Prates (2022) and Santos (2022). Selva’s poetic but not romanticized narratives drive the discussion throughout the text.